Evaluation of LPWAN technology for Smart City - Mroue, Hussein; Andrieux, Guillaume; Motta Cruz, Eduardo; Rouyer, Gilles (EAI Endorsed Transactions on Smart Cities, 2017)
In this paper, we explore technologies for low power wide area networks (LPWAN) serving the Internet of Things (IoT). These networks are ded-icated to long-range and low-speed communication to ensure a good autonomy up to 10 years and a budget link up to tens of kilometers. The performance of two LPWA technologies is investigated, where the well known LoRa and Sigfox technologies are evaluated according to their sensitivity to the interference and the impact of the spreading spectrum technique on the receptor sensitivity. Numerical results are presented and discussed.
Keywords: Low Power Wide Area Networks; Inter-ference; Chirp Spread Spectrum; Ultra-narrow band; Physical layer